Calibration of the paediatric index of mortality in UK paediatric intensive care units. Issue 2 (1st February 2001) - Pearson, G A; Stickley, J; Shann, F
Abstract : AIM: To test a paediatric intensive care mortality prediction model for UK use. METHOD: Prospective collection of data from consecutive admissions to five UK paediatric intensive care units (PICUs), representing a broad cross section of paediatric intensive care activity. A total of 7253 admissions were analysed using tests of the discrimination and calibration of the logistic regression equation. RESULTS: The model discriminated and calibrated well. The area under the ROC plot was 0.84 (95% CI 0.819 to 0.853). The standardised mortality ratio was 0.87 (95% CI 0.81 to 0.94). There was remarkable concordance in the performance of the paediatric index of mortality (PIM) within each PICU, and in the performance of the PICUs as assessed by PIM. Variation in the proportion of admissions that were ventilated or transported from another hospital did not affect the results. CONCLUSION: We recommend that UK PICUs use PIM for their routine audit needs. PIM is not affected by the standard of therapy after admission to PICU, the information needed to calculate PIM is easy to collect, and the model is free.